Vascular perfusion kinetics by contrast-enhanced ultrasound are related to synovial microvascularity in the joints of psoriatic arthritis. Issue 11 (November 2015) - Fiocco, Ugo; Stramare, Roberto; Coran, Alessandro; Grisan, Enrico; Scagliori, Elena; Caso, Francesco; Costa, Luisa; Lunardi, Francesca; Oliviero, Francesca; Bianchi, Fulvia; Scanu, Anna; Martini, Veronica; et al.
Abstract The purpose of the study was to assess the relationship of the continuous mode contrast-enhanced harmonic ultrasound (CEUS) imaging with the histopathological and immunohistochemical (IHC) quantitative estimation of microvascular proliferation on synovial samples of patients affected by sustained psoriatic arthritis (PsA). A dedicated linear transducer was used in conjunction with a specific continuous mode contrast enhanced harmonic imaging technology with a second-generation sulfur hexafluoride-filled microbubbles C-agent. The examination was carried out within 1 week before arthroscopic biopsies in 32 active joints. Perfusional parameters were analyzed including regional blood flow (RBF); peak (PEAK) of the C-signal intensity, proportional to the regional blood volume (RBV); beta (β) perfusion frequency; slope (S), representing the inclination of the tangent in the origin; and the refilling time (RT), the reverse of beta. Arthroscopic synovial biopsies were targeted in the hypervascularity areas, as in the same knee recesses assessed by CEUS; the synovial cell infiltrate and vascularity (vessel density) was evaluated by IHC staining of CD45 (mononuclear cell) and CD31, CD105 (endothelial cell) markers, measured by computer-assisted morphometric analysis. In the CEUS area examined, the corresponding time-intensity curves demonstrated a slow rise time. Synovial histology showed slight increased layer lining thickness, perivascular lymphomonocyte cell infiltration, and microvascular remodeling, with marked vessel wall thickening with reduction of the vascular lumen. A significant correlation was found between RT and CD31+ as PEAK and CD105+ vessel density; RT was inversely correlated to RBF, PEAK, S, and β. The study demonstrated the association of the CEUS perfusion kinetics with the histopathological quantitative and morphologic estimation of synovial microvascular proliferation, suggesting that a CEUS imaging represents a reliable tool for the estimate of the synovial hypervascularity in PsA.